Risk factors for coil protrusion into the parent artery and associated thrombo-embolic events following unruptured cerebral aneurysm embolization - Ishihara, Hideaki (Interv Neuroradiol, 2015)
OBJECTIVE: Advances in vascular reconstruction devices and coil technologies have made coil embolization a popular and effective strategy for treatment of relatively wide-neck cerebral aneurysms. However, coil protrusion occurs occasionally, and little is known about the frequency, the risk factors and the risk of thrombo-embolic complications. METHOD: We assessed the frequency and the risk factors for coil protrusion in 330 unruptured aneurysm embolization cases, and examined the occurrence of cerebral infarction by diffusion-weighted magnetic resonance imaging (DW-MRI). RESULT: Forty-four instances of coil protrusion were encountered during coil embolization (13.3% of cases), but incidence was reduced to 33 (10% of cases) by balloon press or insertion of the next coil. Coil protrusion occurred more frequently during the last phase of the procedure, and both a wide neck (large fundus to neck ratio) (OR = 1.84, P = 0.03) and an inadequately stable neck frame (OR = 5.49, P = 0.0007) increased protrusion risk. Coil protrusions did not increase the incidence of high-intensity lesions (infarcts) on DW-MRI (33.3% vs 29% of cases with no coil protrusion). However, longer operation time did increase infarct risk (P = 0.0003). Thus, tail or loop type coil protrusion did not increase the risk of thrombo-embolic complications, if adequate blood flow was maintained. CONCLUSION: Coil protrusion tended to occur more frequently in cases of wide-neck aneurysms with loose neck framing. Moderate and less coil protrusion carries no additional thrombo-embolic risk, if blood flow is maintained, which can be aided by additional post-operative antiplatelet therapy.